البطريك الماروني أنطوان عريضة وسياسة الإخاء الإسلامي المسيحي 1935-1936 - العاني، سرمد عكيدي فتحي; الربيعي، غصون كريم مجذاب (جامعة الانبار - كلية التربية للعلوم الإنسانية, 2023)
لقد وقع الاختيار على دراسة البطريك الماروني انطوان عريضة وسياسة "الإخاء الإسلامي المسيحي" لأنها من المواضيع البارزة والنادرة في تاريخ لبنان السياسي المعاصر والتي لم تسلط الأضواء عليها بفعل تأثير الأدلجة الطائفية فطمست مواقف البطريركية المارونية الوطنية والقومية، وهي مواقف إنسانية وسياسية واجتماعية مشرفة ومسؤولة في الأزمات الحادة التي واجهها الشعب اللبناني بفعل سياسة الانتداب الفرنسي والتي أسهمت في إجبار الفرنسيين على عقد معاهدة مع لبنان لإعلان استقلاله والجلاء العسكري منه. وقد زاد من أهمية هذه المواقف سياسة البطريك الماروني أنطوان عريضة لشعار (الإخاء الإسلامي - المسيحي) أمام سياسة فرنسا أو حجتها بالدفاع عن الأقليات المسيحية، والتي كانت تهدف أساساً إلى ترسيخ جذور الطائفية في لبنان وتحطيم الوحدة الوطنية. The choice fell on the study of the Maronite Patriarch Antoine Arida and the policy of “Muslim-Christian brotherhood” because it is one of the prominent and rare topics in the contemporary political history of Lebanon, which was not highlighted due to the influence of sectarian ideology, so it obscured the national and national positions of the Maronite Patriarchate, which are human, political and social positions that are honorable and responsible in crises. The acute situation faced by the Lebanese people as a result of the French mandate policy, which contributed to forcing the French to conclude a treaty with Lebanon to declare its independence and the military evacuation from it. The importance of these positions was increased by the policy of the Maronite Patriarch Antoine, petitioning for the slogan (Muslim-Christian brotherhood) in front of France’s policy or argument to defend Christian minorities, which was mainly aimed at consolidating the roots of sectarianism in Lebanon and destroying national unity.
Keywords: الوحدة الوطنية -- الأقليات المسيحية -- الانتداب الفرنسي -- الشعوب اللبنانية